استخدام نماذج box-jenkins في تقدير انتاجية العمل في المصرف التجاري السوري –فرع جبلة- - الرفاعي عبد الهادي; اسبير علا (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The objective of this research is to analyze the time series of labor productivity in the Commercial Bank of Syria for a period of ninety days. The pattern of change in productivity is identified in order to construct a model that helps predict the values ​​of productivity. So we used Box Jenkins models in this study by using statistical methods Such as the ADF, PP KPSS and Q stat tests to detect that the series is Non stationary, but when the first difference was taken, the series becomes stationary, and confirmed by the same previous tests. A series of time series models were then filtered based on Autocorrelation (ACF) and Partial Autocorrelation(PACF). After selecting between several candidate models, by applying some statistical methods such as MSE and BIC, we selected the best time series model ARIMA (1,1,1). The significance of its coefficients was determined using the Ljung box test, and the productivity of the work was predicted for 30 working days. يهدف هذا البحث إلى تحليل السلسلة الزمنية لإنتاجية العمل في المصرف التجاري السوري عن فترة تسعين يوماً, حيث يتم التعرف على نمط تغير الانتاجية من أجل بناء نموذج يساعد على التنبؤ بقيم الانتاجية, وقد تم الاعتماد على منهجية بوكس وجينكنز من خلال تطبيق الأساليب والاختبارات الإحصائية المتعلقة بالسلاسل الزمنية مثل اختبار ADF , PP, KPSS وQ statلنكتشف أن السلسلة غير مستقرة,ولتصبح السلسلة مستقرة تم أخذ الفرق الأول وتم التأكد من استقرارها باعتماد الاختبارات السابقة نفسها, وبعدها تم ترشيح مجموعة من النماذج المعبرة عن السلسلة الزمنية بالاعتماد على شكل انتشار دالتي الارتباط الذاتي ACF والارتباط الذاتي الجزئي PACF, وبعد المفاضلة بين عدة نماذج مرشحة تم اختيار أفضلها بتطبيق بعض المعايير الاحصائية مثل MSE , BIC, تم اختيار أفضل نموذج معبر عن السلسلة الزمنية وهو النموذج ARIMA(1,1,1). وتم التأكد من معنوية معاملاته باستخدام اختبار LjungBox , وبعدها تم التنبؤ بإنتاجية العمل لمدة ثلاثين يوم عمل قادمة.